PEMBUATAN LKPD BERBASIS PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) PADA MATERI USAHA, ENERGI MOMENTUM DAN IMPULS FISIKA KELAS XI SEMESTER 1 - Riri Raihannil Jannah; Yenni Darvina (Universitas Negeri Padang, 2017)
LKDP based cooperative learning type group investigation is LKPD containing the assignment of individuals who are working with a group of measures cooperative learning type group investigation. LKPD based cooperative learning type group investigation is equipped with a scientific step that is contained on the demands of the curriculum in 2013 so that it can be used as teaching materials to be used for class XI physics learning semesters 1. The aim of this study to generate LKPD based cooperative learning type group investigation that valid. The research conducted is a Research and Development (R&D), design study was used to test the validity of the products. As the subject of this study is LKPD physics-based cooperative learning type group investigation. The data collection instrument used in this study is a validation sheet consisting of four indicators are: feasibility content, linguistic components, parts and components kegrafisan presentation. Based on the analysis of data obtained validation LKPD validity to LKPD based cooperative learning type group investigation is valid with the validity of the average assessed by experts is 80.52 with a valid criteria. LKPD based cooperative learning type group investigation can be used as teaching materials are suitable for use in a business matter, energy, momentum and impulse subjects Physics class XI semesters 1.